Augmented Reality for Science Learning in Elementary School: A Literature Review: Analyzing the Effectiveness - Amalia, Alviena Tazky; Kuswandi, Dedi; Ekawati, Ratna; Dewi, Radeni Sukma Indra (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
This article discusses the effectiveness of augmented reality media on science learning in elementary schools. Effectiveness is reviewed from the improvement of student learning outcomes in elementary school science learning. For this reason, augmented reality media appears to provide an interactive and interesting learning experience. Through a systematic literature review on Google Scholar on 7 articles from 2021-2025 which were selected through a screening process through the publish or perish application, the criteria were determined: discussing three keywords, namely augmented reality media, science learning and elementary school, and feasibility. Eligibility filters several aspects 1) minimum article index sinta 3, 2) availability for download in the form of pdf files. After going through the screening process, the results showed that AR media in science learning in elementary schools can significantly improve students' understanding, critical thinking skills, technology skills, learning motivation, and learning outcomes in science learning. This comes from the characteristics of AR media that are easy to integrate with learning models and conventional learning media, besides that augmented reality media is also considered interactive and helps visualize complex images, such as in human organ material, the solar system, landscapes, materials that require visual explanation. Therefore, teachers as educators no longer experience problems explaining material visually, and it is hoped that from this research teachers can also see how effective augmented reality media is in learning science in elementary schools